Growth Response and Yield of Shallots (Allium Ascalonicum L.) on Giving Various Types of Mulch and NPK Fertilizer Doses - Winesih, Winesih; Wijaya, Wijaya; Nur, Subandi (Ann Publisher, 2024)
This study aims to determine the type of mulch and dose of NPK fertilizer that can increase the growth and yield of shallots (Allium ascalonicum L.). The research was conducted in Cibogo Village, Cirebon Regency, West Java. The location is located at an altitude of 30 meters above sea level (m asl), the rain type belongs to type C (slightly wet). The research was conducted from April to June 2021. This study was prepared based on Group Randomized Design (RAK) with 2 treatment factors and 3 repeats. The first factor is the type of mulch and the second factor is the application of NPK fertilizer. The results showed that the combination of rice straw mulch treatment with NPK fertilizer 300 kg / ha had a significant effect on growth components, namely plant height 28 HST, number of leaves aged 42 HST, and a real effect on yield components, namely tuber diameter, fresh weight of tubers per clump and per plot, dry weight of tubers per clump and per plot. The results also showed that the combination of rice straw mulch treatment with NPK doses of 300 kg/ha and 400 kg/ha gave a good average dry weight of tubers per hectare, namely 8.4 tons/ha and 7.9 tons/ha, respectively.